The influence of the sintering system on PMN properties - Cavalheiro, A. A. [UNESP]; Barrionuevo, S. M. [UNESP]; Cilense, M. [UNESP]; Zaghete, M. A. [UNESP]; Varela, José Arana [UNESP] (Trans Tech Publications, 2003)
PMN powder samples with PbO excess of 0, 1,2 and 3% were submitted to the pressing and sintering at 1200°C for 4h with a heating rate of 3°C/min. A new sintering system, developed at our laboratories, was used. It allows obtaining more information on the sintering process. The sintered samples in the new system were compared to sintered samples in the C system. The microstructure, dielectric properties and the effect of the PbO excess in different sintering systems were compared. The N system permitted to obtain a ceramic with better properties, such density, dielectric constant and very homogeneous microstructure.
Keywords: Ceramics; Dielectrics; Microstructure; PMN; Sintering; Lead magnesium niobate; Lead oxide; Pyrochlore phase ratio; Composition effects; Crystal microstructure; Density (specific gravity); Heating; Permittivity; Perovskite; Pressing (forming); Lead compounds